1998
DOI: 10.1103/physrevb.58.7040
|View full text |Cite
|
Sign up to set email alerts
|

Mn ion clustering in II-VI semimagnetic semiconductor heterostructures

Abstract: The results of photoluminescence excitation experiments in Cd 1Ϫx Mn x Te and Zn 1Ϫx Mn x Se diluted magnetic semiconductor quantum-well structures are shown to be consistent with the occurrence of a clustering of the magnetic Mn ions. Possible clustering mechanisms are discussed briefly together with alternative explanations of the data. ͓S0163-1829͑98͒09835-X͔

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…[5][6][7][8] The lattice constants and band parameters of these alloys depend strongly on the concentration of the paramagnetic ions. Also, their magnetic properties are substantially modified in the presence of magnetic impurities.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The lattice constants and band parameters of these alloys depend strongly on the concentration of the paramagnetic ions. Also, their magnetic properties are substantially modified in the presence of magnetic impurities.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the structural data of the samples are summarized in table 1. Photoluminescence emission experiments were carried out at various external magnetic fields in a superconducting magnet at a temperature of 1.8 K. Details of the sample preparation and the results of photoluminescence excitation and reflectivity measurements on the samples can be found in the literature [2][3][4].…”
Section: Methodsmentioning
confidence: 99%
“…Another effect was termed 'alloy clustering' and denotes the occurrence of a non-random distribution of the Mn ions in the crystal [10]. Recently a detailed comparison between theoretical calculations and photoluminescence excitation experiments showed that this effect can alter the effective temperature as well as the effective spin of the Mn ions [2].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…2 These phenomena have also been found in other Mn 2+ activated phosphors and ascribed to the formation of Mn 2+ -Mn 2+ pair centers which exhibit different spectroscopic characteristics, especially much shorter decay time than those of isolated Mn 2+ . [2][3][4][5][6][7] But the reports on the variation of optical properties of BaAl 12 2+ with the increase of Mn 2+ concentration, but they considered that no Mn 2+ -Mn 2+ pairs exist because emission peak shift was not observed by them. 1 However, we do find peak movement in other authors' report though they did not mention it.…”
mentioning
confidence: 94%